Optical solitons for Triki-Biswas equation by two analytic approaches - Aliyu, Aliyu Isa; Alshomrani, Ali S.; İnç, Mustafa; Baleanu, Dumitru (Amer Inst Mathematical Sciences-Aims, 2020)
The present study is devoted to using two analytic approaches to study the Triki-Biswas equation (TBE). The TBE model plays a vital role in propagation of short pulses of width around regions of sub-10 fs in optical. The analytic approaches used are the sine-Gordon expansion (SGEM) and the Riccatti Bernoulli sub-ODE (RBSO) methods. Chirped kink-type, bright envelope and singular solitons are formally derived.
Keywords: TBE; Sine-Gordon expansion method; Riccatti Bernoulli sub-ODE method; optical soliton; chirped kink-type; bright solitons